The Effect of Visfatin on the Functioning of the Porcine Pituitary Gland: An In Vitro Study - Karolina Szymanska; Edyta Rytelewska; Ewa Zaobidna; Marta Kiezun; Marlena Gudelska; Grzegorz Kopij; Kamil Dobrzyn; Ewa Mlyczynska; Patrycja Kurowska; Barbara Kaminska; Anna Nynca; Nina Smolinska; et al. (Cells, 2023)
Visfatin (VIS), also known as nicotinamide phosphoribosyltransferase (NAMPT), is the rate-limiting enzyme in the biosynthesis of nicotinamide adenine dinucleotide (NAD+). Recently, VIS has been also recognized as an adipokine. Our previous study revealed that VIS is produced in the anterior and posterior lobes of the porcine pituitary. Moreover, the expression and secretion of VIS are dependent on the phase of the estrous cycle and/or the stage of early pregnancy. Based on this, we hypothesized that VIS may regulate porcine pituitary function. This study was conducted on anterior pituitary (AP) glands harvested from pigs during specific phases of the estrous cycle. We have shown the modulatory effect of VIS in vitro on LH and FSH secretion by porcine AP cells (determined by ELISA). VIS was also found to stimulate cell proliferation (determined by Alamar Blue) without affecting apoptosis in these cells (determined using flow cytometry technique). Moreover, it was indicated that VIS may act in porcine AP cells through the INSR, AKT/PI3K, MAPK/ERK1/2, and AMPK signaling pathways (determined by ELISA or Western Blot). This observation was further supported by the finding that simultaneous treatment of cells with VIS and inhibitors of these pathways abolished the observed VIS impact on LH and FSH secretion (determined by ELISA). In addition, our research indicated that VIS affected the mentioned processes in a manner that was dependent on the dose of VIS and/or the phase of the estrous cycle. Thus, these findings suggest that VIS may regulate the functioning of the porcine pituitary gland during the estrous cycle.